2020
DOI: 10.3390/nu12072044
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Interventions for Infants with Growth Failure in the First Six Months of Life: A Systematic Review

Abstract: (1) Introduction: Current evidence on managing infants under six months with growth failure or other nutrition-related risk is sparse and low quality. This review aims to inform research priorities to fill this evidence gap, focusing on breastfeeding practices. (2) Methods: We searched PubMed, CINAHL Plus, and Cochrane Library for studies on feeding interventions that aim to restore or improve the volume or quality of breastmilk and breastfeeding when breastfeeding practices are sub-optimal or prematur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 72 publications
1
36
0
5
Order By: Relevance
“…Results suggest this support may be important, particularly for parents of fully breastfed infants during the complementary feeding transition. A recent review of interventions for growth faltering among infants younger than 6 months found mixed results among studies comparing the impacts of formula and breastmilk on growth among children with growth failure or other nutritional risks (23). Similar to the results in this study, another review found that formula contributed to faster and more linear growth among pre-term and low birthweight infants than breastmilk (24); however, these prior results are not directly comparable to those of the present study because the prior study did not include full term and normal birthweight infants while the present study did.…”
Section: Discussionmentioning
confidence: 99%
“…Results suggest this support may be important, particularly for parents of fully breastfed infants during the complementary feeding transition. A recent review of interventions for growth faltering among infants younger than 6 months found mixed results among studies comparing the impacts of formula and breastmilk on growth among children with growth failure or other nutritional risks (23). Similar to the results in this study, another review found that formula contributed to faster and more linear growth among pre-term and low birthweight infants than breastmilk (24); however, these prior results are not directly comparable to those of the present study because the prior study did not include full term and normal birthweight infants while the present study did.…”
Section: Discussionmentioning
confidence: 99%
“… 18 The World Health Organization (WHO) feeding guidelines for LBW infants were published in 2011 19 ; however, most of the recommendations are based on low quality evidence; even so, the majority of available evidence was from high-income countries, and most data were limited to very LBW infants (<1.5 kg) even though the majority of LBW infants are born between 1.5 kg to <2.5 kg. 12 20 …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, LBW infants face increased risks for morbidity, neurodevelopmental impairments and growth faltering as well as challenges related to breast feeding, particularly its initiation and exclusivity in early infancy 2 8–12. Inadequate and insufficient feeding contributes to poor growth outcomes, such as stunting, wasting and underweight, for which the risk among LBW infants is already increased 13.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though many of the recommendations in these WHO guidelines were ‘strong’, the underlying evidence-base was recognised as being sparse and overall low quality. Many research and programmatic gaps remain (9, 10).…”
Section: Introductionmentioning
confidence: 99%